Educating in emotions: A challenge to integration - Rodríguez Chávez, Miriam Soledad (2008)
The strong boost the integration programs have received in Chile during the last years, in order to students with Special educational Needs (N.E.E- in Spanish) may access to regular schools, implies a series of challenges and new questions which would not be effectively answered for an integration of quality. Emotional intelligence is the focus of our research. This is an exploratory and descriptive study with theoretical and practical base of four integrated students, of both genders, who are in basic level of education, and who are from different social strat, belonging to different communes of Santiago de Chile. Finally, we emphasize, the most current existing programs.